Ownership Structure, Capital Structure, and Their Impact on Financial Performance - Waluyo, Christopher Glenn Caesar; Kirana, Nanda Wahyu Indah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study aims to analyze the effect of concentrated ownership, managerial ownership, and capital structure on the financial performance of companies in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. This study provides empirical insight into how ownership structure and funding policies affect company profitability amid economic dynamics and competition in Indonesia's banking industry. A quantitative approach was used, with panel data regression analysis in EViews version 13, based on secondary data from the annual financial reports of the sample companies. The concentrated ownership is measured as the percentage of the largest institutional shareholding. The managerial ownership variable is measured by the proportion of shares owned by management. The DER ratio represents capital structure. Financial performance is measured using the ROA profitability ratio. Their results show that concentrated ownership and capital structure have significant effects on company financial performance, whereas managerial ownership does not.